Analisis Peran Manajemen Pelayanan dan Lingkungan Kerja terhadap Kinerja Pegawai pada Kantor Kecamatan Pemerintah Kota Makassar - Gunawan, Hendra (Movere Journal, 2025)
This study aims to analyze the influence of service management and work environment on employee performance in the Makassar City Government District Office. The research sample consisted of 125 employees in 15 sub-districts who were selected using the purposive sampling technique. Quantitative data were collected through questionnaires and analyzed using Smart PLS, while qualitative data was obtained through in-depth interviews with key informants and analyzed thematically using NVivo.The results show that service management has a positive and significant influence on employee performance, with indicators of clarity of procedures and training as the main contributors. The work environment also has a significant and more dominant influence, highlighting the importance of physical facilities, harmonious working relationships, and managerial support in improving employee performance. These two variables have been proven to contribute synergistically to increasing work effectiveness in the public sector. This research makes an academic contribution by supporting literature on the importance of service management and the work environment in improving employee performance. Practically, this study recommends local governments to strengthen the managerial system and create a conducive work environment to improve the quality of public services. The results of this research are expected to be a strategic reference for human resource management policies in the government sector.